2022
DOI: 10.3390/vaccines10050656
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Immunologic Efficacy of the Recombinant Adenovirus Type-5-Vectored (CanSino Bio) Vaccine in University Professors during the COVID-19 Delta Wave

Abstract: Information regarding the efficacy of the recombinant adenovirus type-5-vectored (CanSino Bio) vaccine against the COVID-19 disease in a real-life setting is limited. A retrospective cohort study was carried out in the teaching university community of the metropolitan area of Monterrey, Mexico, through a four-section survey, and during the COVID-19 delta wave. Determination of IgG antibodies against SARS-CoV-2 spike (S) protein was performed in a subset of participants vaccinated with CanSino Bio. A total of 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Also, these data can support a previous study in the Mexican population reporting that SARS-CoV-2 breakthrough infections during the Delta wave in a Mexican hospital mainly occurred in patients vaccinated with the Ad5-nCoV vaccine compared to those vaccinated with other platforms. Moreover, they suggested that a booster dose of the Ad5-nCoV vaccine is advisable for those individuals without previous infection to improve their immune response against SARS-CoV-2 [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, these data can support a previous study in the Mexican population reporting that SARS-CoV-2 breakthrough infections during the Delta wave in a Mexican hospital mainly occurred in patients vaccinated with the Ad5-nCoV vaccine compared to those vaccinated with other platforms. Moreover, they suggested that a booster dose of the Ad5-nCoV vaccine is advisable for those individuals without previous infection to improve their immune response against SARS-CoV-2 [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following this side effect of the administration of this vaccine, the FDA and CDC recommended stopping the administration of this vaccine [ 254 , 255 ]. Other vaccines which are used outside the US include AstraZeneca, Sputnik-V, and CanSino which are vector-based vaccines and an inactivated whole-virus SARS-CoV-2 vaccine (by Bharat Biotech and Sinovac) [ 256 , 257 ]. Here, we summarize the different types of COVID-19 vaccine candidates and clinical trials.…”
Section: Vaccine Developmentmentioning
confidence: 99%
“…Recombinant COVID-19 vaccine (adenovirus type 5 vector): Convidecia. Convidecia uses a third-generation novel coronavirus technology to produce humoral and cellular immunity (Zhu et al 2020a(Zhu et al , 2020b(Zhu et al , 2022bWu et al 2021;Halperin et al 2022;Richardson et al 2022;Guzmán-López et al 2022;. The vaccine can be stored between 2°C and 8°C.…”
Section: Covid-19 Vaccines (I)mentioning
confidence: 99%